2017
DOI: 10.22401/jnus.20.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization a New 1,3-Diazepine Compounds from New Bis 4-Amino-3-Mercpto-1,2,4-Triazole Derivatives

Abstract: Compounds with two triazole rings IVa,b were synthesized through the reaction of diacid hydrazide firstly with CS 2 /KOH, and secondly with excess of hydrazine hydrate. The one-step reaction of isatin with benzylidene benzeneamine (S 1 -S 10 ) in ethanol gave 2-Ar-3-Ar' [3,4b]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The results of FT-IR, 13 C-NMR, and 1 H-NMR showed that the target molecules were formed due to the least obstructive effect in all preparation processes. Generally, N 9 is the best derivative that has significantly (p<0.01) recorded a stronger influence to inhibit growth of Candida sp.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of FT-IR, 13 C-NMR, and 1 H-NMR showed that the target molecules were formed due to the least obstructive effect in all preparation processes. Generally, N 9 is the best derivative that has significantly (p<0.01) recorded a stronger influence to inhibit growth of Candida sp.…”
Section: Resultsmentioning
confidence: 96%
“…The structural formula, names, melting points, colors, and percentage of yields for the synthesized azomethine compounds are recorded. [12][13][14][15][16][17][18][19] General procedure for synthesis of oxazepine compounds N 6 -N 10 Equimolar mixtures 0.01 mol of azomethine compounds and phthalide compound dissolved in 30 ml of tetrahydrofuran was placed in a 100-ml roundbottom flask equipped with condenser and stirrer bar presence trace of glacial acetic acid as a catalyst was added. The reaction mixture was refluxed for 3 hour, and left to stand for 24 hour and then solid product was precipitated.…”
Section: General Procedures For Synthesis Of Azomethine Compounds N 1 mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] For example, the reaction of phthalic anhydride with N-(4-(dimethylamino) benzylidene) thiophen-2-amine in dry benzene gave an 1,3-oxazepine derivaties (Scheme 4).…”
Section: Scheme 3 Structures Of Oxazepinesmentioning
confidence: 99%
“…The yields, elemental analytical, FT-IR, ) [15]. FTIR data for M1-M4 are tabulated in Table 1. 1 H-NMR for Schiff bases spectra exhibited pure singlet signal within range of δ= 8.67-8.69 ppm attributed to protons for azomethine group and set of signals within range of δ =7.09-8.2 ppm attributed for aromatic protons [16][17].…”
Section: Characterization Of M 5 -M 12 Compoundsmentioning
confidence: 99%
“…Oxazepine was synthesized by cycloaddition reaction which is a type of pericyclic reaction [2].The importance of 1,3-oxazepine is ascribed to their applications as anticonvulsant [3][4][5][6][7], antidepressant [8], skeletal muscle relaxants [9], neuroleptic [10], antitumor agent [11], antibacterial [12], anti-corrosion [13], anti-anxiety [14]. Many researchers were reported the synthesis of 1,3-oxazepine by either maleic anhydride or phthalic anhydride [15][16][17].The novelty of the present paper is the synthesis two core 1,3-oxazepine in same molecule by using substitute phthalic anhydrides and DFT Study of 4,4′-oxydianiline Imines as precursors of tetrahalo-1,3-oxazepine to calculate the energies of the HOMO and LUMO orbitals used to predict some physical properties of Schiff bases M1-M4, such as hardness, electron affinity A, Ionization potential I, absolute electronegativity μ, absolute hardness η, and electrophilicity w, stability and aromaticity.…”
Section: Introductionmentioning
confidence: 99%